Efektivitas Metaverse Tourism Sebagai Sarana Promosi Wisata Bali - Rizki Nurul Nugraha; Eka Syah Putra (Jurnal Ilmiah Wahana Pendidikan, 2023)
Excursion Metaverse Tourism is likened to using technology to create a real earth (body) experience in virtual space. The virtual world of tourisrn has opened up new opportunities to revolutionize the enjoyment of travel. The adaptation of Metaverse Tourism using VirtuaI ReaIity (VR) and Augrnented ReaIity (AR) leads to “high-tech and high-touch” collaboration, an almost essential tourism principle. Bali has great potential to take advantage of rnetaverse tourism as a means of promoting natural shark tourism that stops at TNTC. The number of excursion tours that previously reached more than 4,000 people will decrease to 68 people on travel and research missions in 2021. This research uses a quaIitative descriptive method that increases references with low quality information and questions and answers and validates information. studied during the research. By adopting technology that is environrnentaIIy friendIy and has a positive irnpact on nature conservation, tourists' interest in natural phenomena is reduced and they don't have to worry about the negative issues of traveling in Bali.